MEDIATION TASKS ACROSS ELT RESOURCES: AN ANALYSIS WITHIN THE CEFR-CV FRAMEWORK. - LUÍS, ANA R. (Biblos: Revista da Faculdade de Letras da Universidade de Coimbra, 2024)
Mediation is recognised as one of the four modes of communication defined by the Common European Framework of Reference for Languages (Council of Europe, 2001), alongside reception, production and interaction. It emphasises the need for learners to act as intermediaries, enabling effective communication across linguistic and cultural barriers, whether within the same language or across different languages. Despite its critical importance within plurilingual and intercultural school contexts, mediation has received little attention in English language education, particularly within the Portuguese context. To better understand how students' mediation skills might be improved, this study aims to document and analyse the integration of mediation tasks in two recently published English textbooks, drawing on the conceptual framework outlined in the Companion Volume (Council of Europe, 2020).